Politik Identitas Dalam Masyarakat Multikultural : (Studi Kasus Politik Sosial di Indonesia) - Munandar, Aris; Susanti, Endang (CV. Lentera Literasi Indonesia, 2025)
This research aims to analyse the role of identity politics in Indonesia's multicultural society and its impact on social and political dynamics, particularly through social media in political campaigns. In Indonesia, which has high ethnic, religious and cultural diversity, political parties and legislative candidates often utilize identity politics to mobilise support from certain groups. Social media, as a key platform in modern political campaigns, plays an important role in reinforcing or defusing identity-based social polarisation. This research uses a literature study approach to review literature related to identity politics, social conflict, and the impact of social media in strengthening or defusing tensions between groups. The results show that identity politics, while it can strengthen solidarity within certain groups, also has great potential to increase social polarisation to the detriment of social cohesion. Intensive identity-based campaigns on social media often exacerbate tensions between ethnic or religious groups, which risks undermining national political stability. This research also found that while social media can exacerbate social divisions, it also has the potential to ease tensions through inclusive narratives that reinforce pluralism. Overall, this research provides insight into the challenges and opportunities faced in managing identity politics in Indonesia, as well as how social media can be used wisely to maintain political and social stability.